Laryngo-Tracheal Scleroma- A Case Report - Siddiquee, Belayat Hossain; Datta, Pran Gopal; Alam, Md Sahbub; Dey, Ashok Kumar (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Scleroma is a granulomatous condition of the nose and other parts of the respiratory tract, usually primarily affects the nose and the nasopharynx (Rhinoscleroma). But rarely they also occur in the larynx (secondary to rhinoscleroma or primary laryngeal affection). This is endemic in Eastern Europe, North Africa, Southern Asia and Central America. In Bangladesh this is almost clinically unknown but theoretically possible. Presented case of laryngo-tracheal scleroma is possibly the first ever reported one from Bangladesh. The main presentation of this patient was laryngeal obstruction simulating malignancy and finally demanded tracheostomy. Only post surgical histopathology report could reveal the diagnosis. Key words: Scleroma, Laryngeal scleroma. DOI: 10.3329/jbcps.v27i1.4244 J Bangladesh Coll Phys Surg 2009; 27: 49-51